Methodology for correcting the nonlinear response of radionuclide calibrators - Daniel da Silva Quaresma; Antônio Eduardo de Oliveira; Akira Iwahara; Paulo Gonçalves da Cunha (Brazilian Journal of Radiation Sciences)
Due to constructive and operational issues, the response of a radionuclide calibrator used in Nuclear Medicine can behave in a non-linear manner, especially in the transition of scales. Although the deviations from linearity are small, they may be important for standard secondary or reference radionuclide calibrators used in calibration laboratories. In the document TRS 454 - IAEA it is proposed that the deviation from linearity for these instruments should be in the range of ± 2%. However, calibration laboratories may have some difficulty meeting the requirement. This article proposes an easy-to-implement methodology to correct the response of reference radionuclide calibrators from calibration laboratories, in order to meet the requirement of ± 2% for the linearity parameter recommended by the IAEA.